2016
DOI: 10.1186/s13069-016-0046-0
|View full text |Cite
|
Sign up to set email alerts
|

Matrix and cell phenotype differences in Dupuytren’s disease

Abstract: BackgroundDupuytren’s disease is a fibroproliferative disease of the hand and fingers, which usually manifests as two different phenotypes within the same patient. The disease first causes a nodule in the palm of the hand, while later, a cord develops, causing contracture of the fingers.ResultsWe set out to characterize the two phenotypes by comparing matched cord and nodule tissue from ten Dupuytren’s patients. We found that nodule tissue contained more proliferating cells, CD68-positive macrophages and α-smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…We found an increased expression of Wnt4, b-catenin and YAP1 in plaques, and observed changes related to collagen quantity and quality. Part of our findings coincide with recent observations in DD [27][28][29], underscoring a certain relationship between both disease states. We obtained plaque and unaffected tissue from the tunica albuginea of the same patient, and by doing so, we excluded inter-individual variations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found an increased expression of Wnt4, b-catenin and YAP1 in plaques, and observed changes related to collagen quantity and quality. Part of our findings coincide with recent observations in DD [27][28][29], underscoring a certain relationship between both disease states. We obtained plaque and unaffected tissue from the tunica albuginea of the same patient, and by doing so, we excluded inter-individual variations.…”
Section: Discussionsupporting
confidence: 92%
“…As the main constituents in fibrotic tissues are collagen and fibronectin, the decreased expression of fibronectin will contribute to a different composition of the extracellular matrix in plaque. Differences in fibronectin mRNA expression have also been observed between the cord and the nodule in DD [29], whereas no differences were seen in mRNA levels among elastin, decorin, biglycan, and fibromodulin, which is similar to what we observed in PD.…”
Section: Discussionsupporting
confidence: 88%
“…Dupuytren's disease is a fibromatosis of the connective tissue of the palm that can lead in certain cases to the immobility of one or more fingers due to formation of nodules and cords in the palmar fascia . Connective tissue represents the architectural and supportive framework of many tissue and organs in animal body, and it is mainly composed by fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…but not COL1A2 mRNA in Dupuytren's tissue, as compared to shoulder capsule (Kilian et al, 2007). In the present study, we did not distinguish between nodule and cord for RNA analysis, although a prior study found both COL1A1 and COL1A2 mRNA was higher in nodule as compared to cord, despite lower collagen (I) protein being present in nodule (van Beuge et al, 2016).…”
Section: Discussionmentioning
confidence: 60%